If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 = 1 + 3n + -2 Reorder the terms: 8 = 1 + -2 + 3n Combine like terms: 1 + -2 = -1 8 = -1 + 3n Solving 8 = -1 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 8 + -3n = -1 + 3n + -3n Combine like terms: 3n + -3n = 0 8 + -3n = -1 + 0 8 + -3n = -1 Add '-8' to each side of the equation. 8 + -8 + -3n = -1 + -8 Combine like terms: 8 + -8 = 0 0 + -3n = -1 + -8 -3n = -1 + -8 Combine like terms: -1 + -8 = -9 -3n = -9 Divide each side by '-3'. n = 3 Simplifying n = 3
| 8=1+32-2 | | 5*3/5*7 | | 7t+9-4t+3= | | -10x-20-12x+15=97 | | 150d-600=270 | | -7x+41+4x=34 | | 56Y^9/7y^7 | | 4.5x+3=2.55 | | X-70+4x=60 | | 14-(3a+2)=14-3a-2 | | 37z+4z= | | 5(x+4)=7x-21 | | 5(z+5)= | | 3d+8=2-7 | | -15=b-6-3 | | x-0=-2 | | 0.9-3=0.6 | | (13)-(x+1)=2(3x-1) | | 3(4x-6)-(x-2)= | | 4(n+3)=5(n-3) | | 4-(3x+2)=7x-2(4x-3) | | 3+5(4+2)= | | 6-3+5=3+5 | | 3x-22=2+3 | | -22+8x-4x=30 | | 5x+3-2x=7-4x+1 | | 4/x^6y^6*4x/y^4 | | 2.5x-13=2 | | 2e(x+2)=5 | | u^2+3u+uv+3v=0 | | X-12+x=38 | | X-13=6+2x |